Uncommon Cases of Venous Thromboembolism - Bosevski, Marijan; Bojovski, Ivica; Vuchinikj, Aleksandra Gulevska; Anguseva, Tanja; Taleski, Jane; Dimitrovska, Biljana; Sheshoska, Hristina Chamovska; Taneska, Natasa; Jovchevska, Simona; Konjanovski, Tomi; Zhaku, Vegim; Jovanoski, Mario; et al. (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/Walter de Gruyter GmbH, 2023)
There is a growing incidence of new cases of venous thromboembolismworldwide.Some of these patients do have a predisposition to the development of thrombosis, some of them do however have various risk factors associated with this event, but few of them have unrecognized etiology. This paper aimsto describe different scenarios of venous thromboembolism.